What are the challenges faced by widening participation students in the transition period before starting university? Experiences of students waiting to take up a place at a Russell Group University - George, Tracey (2011)
Objective: Research has shown that widening participation students can encounter many barriers on their journey to higher education. Some manage to overcome them, gain a place at university, and go on to achieve academic success; others fall at the last hurdle, dropping out before commencing their course. This research addresses a gap in the current evidence by finding out about the challenges students face in the period before starting university which might contribute to them not registering for their place.